2021
DOI: 10.1111/ijfs.15425
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of hemp protein concentrate obtained by alkaline extraction and successive ultrafiltration and spray‐drying

Abstract: Hemp protein concentrates were obtained from hemp seed cake by extraction at high alkaline pH (10 and 12) followed by an ultrafiltration/diafiltration (UF) purification step and spray-drying. The composition, thermal, nutritional, and functional properties of the resulting protein samples were evaluated. The UF treatment increased protein purity of the protein extracts recovered at pH 10 and 12, from ~61% and ~70% to ~85% and ~88%, respectively. This protein enrichment did not change the polypeptide compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The significant increase for tryptophan, phenylalanine, and tyrosine in the case of MPC for treated sample was detected at 380 nm. A similar pattern was seen in the case of soy protein isolates and hemp seed protein isolates . Therefore, by following fluorescence intensity and maximum wavelength (λ max ), changes in the protein tertiary structure can be identified .…”
Section: Resultssupporting
confidence: 61%
“…The significant increase for tryptophan, phenylalanine, and tyrosine in the case of MPC for treated sample was detected at 380 nm. A similar pattern was seen in the case of soy protein isolates and hemp seed protein isolates . Therefore, by following fluorescence intensity and maximum wavelength (λ max ), changes in the protein tertiary structure can be identified .…”
Section: Resultssupporting
confidence: 61%
“…Hemp has been a valuable food source throughout history, as evidenced by the hemp seeds in China, where roasted hemp seeds can still be bought on the street as snacks (Cerino et al ., 2021). Since the nineties, there has been growing research interest in hemp as an ingredient in food products (Taaifi et al ., 2021, Aiello et al ., 2020, Potin et al ., 2022). Table 1 displays previous studies on the use of hemp in food systems and its functional effects.…”
Section: Utilisation Of Hemp‐derived Phytochemicals and Hemp Extracts...mentioning
confidence: 99%
“…Evidence also suggests that hydrolysed hemp seed proteins have antihypertensive effects (Aiello et al ., 2020). Hemp seed can be used to make flour with valuable nutritional properties, and previous reviews have illustrated potential uses in food systems to aid nutritional well‐being (Taaifi et al ., 2021, Potin et al ., 2022). Previous studies showed that, in optimal quantities, hemp flour added to wheat flour improves the nutritional value and effect physical and sensory characteristics (Pojić et al ., 2015, Apostol et al ., 2015, Rusu et al ., 2021).…”
Section: Utilisation Of Hemp‐derived Phytochemicals and Hemp Extracts...mentioning
confidence: 99%
See 1 more Smart Citation
“…Spray drying is a preservation and controlled release technology that is commonly applied in the food industry [ 10 , 19 , 20 , 21 ], mainly due to being a relatively low-cost technique that is reproducible, rapid, and easy to scale-up, when compared with other microencapsulation technologies [ 22 , 23 ]. Spray drying has been used in the food science field to encapsulate flavours, bioactive and functional compounds, probiotics, enzymes, or even cells [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. A crucial step in developing spray-dried microcapsules for food applications is the choice of the encapsulating material, since its properties (i.e., solubility and emulsifying properties) determine the encapsulation efficiency and stability of the microcapsules [ 34 ].…”
Section: Introductionmentioning
confidence: 99%